SPECIFICS OF THE DEVELOPMENT OF ECONOMIC DIPLOMACY IN GERMANY (World Economics and Finance Bulletin, 2022)
Support and assistance to foreign economic activity, primarily the development of national exports in Germany, is provided by state, public, and private structures: Federal and state parliaments; Federal and land ministries; Federal Department of Economics and Export Control; Federal Wholesale and Foreign Trade Union of Germany, Federal Union of German Industry, Union of Agricultural Producers of Germany, etc., Associations: Federal Association of Industrial and Commercial Chambers; representative offices of industrial and commercial chambers abroad, for example, the Office of the Delegate of the German Economy; land Chambers; Eastern Committee of the German Economy; financial and credit institutions, etc.